Analisis Spektrofotometri Serapan Atom pada Penjernihan Air Sumur Bor di Desa Sekernan - Abul Ainin Hapis; Mukhlis Sanuddin (Universitas Batanghari Jambi, 2022)
Cloudy borehole water if done by filtering method with filtration by sand, charcoal, palm fiber, coral and husks can produce clear water. In the purification process can remove turbidity, color, metal Mn about 98.66 % and Fe around 99,50 %. Zeolite is a mineral that is used as an adsorbent, ion exchanger or catalyst. Zeolite in rice husk ash contains high silica content of 87%-97% and coal ash 50%-69% which is used as an ingredient in the manufacture of zeolite. This study aims to determine the zeolite made from rice husk ash and coal can reduce Fe and Mn levels. Based on the test results of the Health Laboratory Office, samples of water from drilled wells in Sekernan village, RT. 11 with the results of Fe content of 0.475 mg/l and Mn content of 0.380 mg/l. The use of borehole water which has a high metal content for drinking water, bathing and washing can cause a person to suffer from stomach ailments such as diarrhea, skin diseases, such as itching and so on. This research is an experimental study. The results of the water filtration process are left for 30-60 minutes. Furthermore, the water was tested for Fe and Mn levels using Atomic Absorption Spectrophotometry (AAS). The results of the AAS analysis showed that the previous Fe level decreased from 0.475 mg/l to < 0.08 mg/l and the previous Mn level was 0.380 mg/l to < 0.03 mg/l. The purification of borehole water with filtration method can produce clear water. Analysis of the AAS test made from zeolite can reduce the metal content of Mn by about 98.66% and Fe by about 99.50%.